Tips to avoid weak scientific English - Vanelli, Maurizio (Acta Biomedica Atenei Parmensis, 2021)
In the present issue of Acta Biomedica is published a contribution of Rago V on "Scientific writing like a native English-speaker: tips for Italian researchers". The Author, over the past years, has collaborated with Italian researchers and has generally noticed that their English  status is relatively weak. Therefore, he gives "tips or dritte that do not always refer to incorrect English, but rather to weak scientific English" (1). [...]